Aktivitas Fisik Dan Neuro-Longevity: Pendekatan Gizi Dan Promosi Kesehatan Untuk Healthspan - Nurussyariah; Nurul Ichsania (PT Mediatama Zayna Indonesia, 2026)
Neuro-longevity has emerged as an important concept in promoting brain health and extending healthspan through healthy lifestyle behaviors. Physical activity, adequate nutrition, and health promotion are recognized as key factors that support cognitive function and long-term neurological well-being. This study aimed to analyze the relationship between physical activity, nutritional status, and healthspan literacy with neuro-longevity among basketball athletes. An analytical observational study with a cross-sectional design was conducted involving 46 male and female athletes from the Old School and Flying Wheel basketball clubs, ranging from U-16 to general age categories. Data were collected using non-laboratory methods through the International Physical Activity Questionnaire-Short Form (IPAQ-SF), Semi Quantitative - Food Frequency Questionnaire (SQ-FFQ), and a healthspan literacy questionnaire. Neuro-longevity was assessed using a cognitive health and healthy lifestyle questionnaire. Data were analyzed using the Chi-square test with a significance level of p<0.05. The results showed significant associations between physical activity (p=0.001), nutritional quality (p=0.001), healthspan literacy (p=0.002), and neuro-longevity. Athletes with higher physical activity levels, better nutritional quality, and higher healthspan literacy demonstrated more optimal neuro-longevity. These findings highlight the importance of integrating physical activity, nutrition, and health promotion to support brain health and enhance healthspan.